Sociodemographic inequalities in breast cancer screening attendance in Germany following the implementation of an Organized Screening Program: Scoping Review - Núria Pedrós Barnils; Victoria Härtling; Himal Singh; Benjamin Schüz (BMC, 2024)
Abstract Background Organized breast cancer screening (BCS) programs are effective measures among women aged 50-69 for preventing the sixth cause of death in Germany. Although the implementation of the national screening program started in 2005, participation rates have not yet reached EU standards. It is unclear which and how sociodemographic factors are related to BCS attendance. This scoping review aims to identify sociodemographic inequalities in BCS attendance among 50-69-year-old women following the implementation of the Organized Screening Program in Germany. Methods Following PRISMA guidelines, we searched the Web of Science, Scopus, MEDLINE, PsycINFO, and CINAHL following the PCC (Population, Concept and Context) criteria. We included primary studies with a quantitative study design and reviews examining BCS attendance among women aged 50-69 with data from 2005 onwards in Germany. Harvest plots depicting effect size direction for the different identified sociodemographic inequalities and last two years or less BCS attendance and lifetime BCS attendance were developed. Results We screened 476 titles and abstracts and 33 full texts. In total, 27 records were analysed, 14 were national reports, and 13 peer-reviewed articles. Eight sociodemographic variables were identified and summarised in harvest plots: age, education, income, migration status, type of district, employment status, partnership cohabitation and health insurance. Older women with lower incomes and migration backgrounds who live in rural areas and lack private insurance respond more favourably to BCS invitations. However, from a lifetime perspective, these associations only hold for migration background, are reversed for income and urban residency, and are complemented by partner cohabitation. Finally, women living in the former East German states of Saxony, Mecklenburg-Western Pomerania, Saxony-Anhalt, and Thuringia, as well as in the former West German state of Lower Saxony, showed higher BCS attendance rates in the last two years. Conclusion High-quality research is needed to identify women at higher risk of not attending BCS in Germany to address the existing research's high heterogeneity, particularly since the overall attendance rate still falls below European standards. Protocol registration https://osf.io/x79tq/ .